Is Low-Fat Dairy an Appropriate Recommendation for Children? - Ng, Natalie Xiao-Wen; Gross, Susan Michelle (JAMA pediatrics, 2025)
This viewpoint explores the evidence behind recommendations for low-fat dairy consumption in children.